국내 40세 이상 위암 환자의 성별에 따른 혈액생화학적 특성, 영양섭취비교: 제7기(2016-2018) 국민건강영양조사 자료를 이용한 횡단연구 - 이현주; 오성원; 김숙배; Hyeon-Ju Lee; Sung-Won Oh; Sook-Bae Kim (Korean journal of community nutrition, 2023)
Objectives: The purpose of this study was to compare the sex-associated differences in the dietary intake of gastric cancer patients in Korea. Methods: Data from the Korea National Health and Nutrition Examination Survey (KNHANES) the 7th (2016-2018) were analyzed in the present study. The subjects included 122 gastric cancer patients aged over 40 years (75 male, 47 female). General characteristics (age, marital status, household income, education, food security, comorbidities, alcohol drinking, and smoking), anthropometric characteristics (height, weight, body mass index, and blood pressure), blood biochemical characteristics [fasting plasma glucose (FPG), blood urea nitrogen (BUN), creatinine, triglyceride, total cholesterol, and HDL-cholesterol)], and quantity and quality of dietary intake were compared between male and female participants. Results: Males had higher rates of having a spouse, prevalence of hypertension, alcohol drinking, and smoking than females. The proportion of males with a normal range of FPG, BUN, and HDL-cholesterol was lower than that in females. The total cholesterol levels above the normal range were higher in females than in males. We also found that females had a higher percentage of intakes below the estimated energy requirement (EER) and intakes below the estimated average requirement (EAR) for carbohydrates, niacin, phosphorus, and iron than males. The index of nutritional quality (INQ) for phosphorus and folate, nutrient adequacy ratio (NAR) for vitamin C, thiamine, niacin, folate, calcium, and phosphorus, and the mean adequacy ratio (MAR) were lower in females than males. Conclusions: In Korean gastric cancer patients, management of comorbidities such as diabetes and hypertriglyceridemia, lowering FPG, and raising HDL-cholesterol level management is required for males, whereas management of lowering total cholesterol and raising hematocrit is required for females. The quantitative and qualitative nutritional intakes were poor in gastric cancer patients, especially in females, who had a lower nutritional intake than males. We suggest that nutritional interventions are needed to improve the overall nutritional intake in both male and female gastric cancer patients. In particular, we propose that support is urgently needed for females whose nutritional intake is lower than that of males. In addition, family, social, and national support for nutritional management of female gastric cancer patients is highly necessary.